Alcohol exposure during pregnancy altered childhood developmental trajectories in a rural South African community. (9th August 2017) - Davies, Leigh‐Anne; Cockcroft, Kate; Olinger, Lynda; Chersich, Matthew; Urban, Michael; Chetty Makkan, Candice M.; Turnbull, Oliver H.; Olivier, Leana; Viljoen, Denis
Abstract: Aim: This study examined the effects of prenatal alcohol exposure on childhood development trajectories in a rural South African community between 2003 and 2008. Methods: We assessed 121 children at 7–12 months (year one) and 5–6 years (year five) using the Griffiths Mental Developmental Scales – Extended Revised, which measures sensorimotor, cognitive and social development, with lower scores indicating developmental delay. We also interviewed their mothers or caregivers. Three groups were identified: 29 with foetal alcohol syndrome (FAS) or partial FAS (pFAS), 57 more who had been exposed to alcohol and 35 controls who had not. Results: The scale's total score was higher in the controls than in the FAS/pFAS group at year one and year five and in the alcohol‐exposed group at year five. Many groups' trajectories declined when compared with global norms, but the trajectories in the FAS/pFAS and the alcohol‐exposed groups declined more than the controls for eye‐hand and performance and total score. Earlier pregnancy recognition in the FAS/pFAS group correlated strongly (r = −0.77) with higher GQ in year five. Conclusion: FAS/pFAS and prenatal alcohol exposure affected the Griffiths scores more than the control group. Efforts are needed to detect pregnancy early and reduce alcohol exposure.